A Minimum Data Set Of Radiology Reporting System For Exchanging With Electronic Health Record System In Iran - Maryam Ahmadi; Azadeh Bashiri (Tehran University of Medical Sciences, 2014)
Background and Aim: In order to better design an electronic health record system in the country, determining standardized data elements for creating an integrated information system is important. In this study, the minimum data set of radiology reporting system is determined.  Materials and Methods: In this descriptive cross-sectional study, 13 radiologists, 3 anesthesiologists, 3 general practitioners and 3 insurance experts working in the Imaging Center of Imam Khomeini hospital in Tehran were chosen. The research tool was a questionnaire having 11 parts. Content validity and test-retest method were used to measure the validity and reliability of the questionnaire, respectively. Data analysis was performed using the SPSS software. Results: The highest means reported were radiologists' written explanations and suggestions (9.6), image interpretation (9.5), the name of contrast material (9.4), the name of imaging procedure (9.3) type and date of previous measures (9.1), and the final diagnosis (9) and the lowest averages belonged to referring physician's address (4.8), relationship between patients and the primary individual insured (4.3), and religion (2.2). Conclusion: In an electronic health record system, due to the importance of radiology reports for the diagnosis and future management of a patient's clinical problems, it is necessary to pay attention to the minimum set of data related to these reports such as administrative, insurance, patient identity, and clinical data, and the results of radiological examinations for exchanging with electronic health record system.